2020
DOI: 10.1088/1755-1315/575/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of peatland chemicals and their association with the diversity of dominant plants in Papua

Abstract: Peatlands are often associated with an area that has a specific habitat in a particular area. The purpose of this study was to determine the characteristics and associations of the dominant biodiversity in the Mappi Regency, Papua. The research method used was a survey. The survey was conducted in Bamgi District, Mappi, Papua. The results showed that peat soils in Mappi have characteristics that are categorized as fabric-peat. Acidity or soil pH condition belongs in the low category (3.95-4.53), moderate C-org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…This could be understood since the amount of total-N in a soil conversely correlates to the amount of OM as a source of N and C. When OM is oxidized, C content decreases (emitted as CO 2 ), therefore, total-N increases. This findings complemented the outcome of Tanjung et al[12]. They found that Papuan peat soil contained a moderate C-organic (16.31%), high nitrogen (1.09%) and moderate C/N ratio (15.01).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This could be understood since the amount of total-N in a soil conversely correlates to the amount of OM as a source of N and C. When OM is oxidized, C content decreases (emitted as CO 2 ), therefore, total-N increases. This findings complemented the outcome of Tanjung et al[12]. They found that Papuan peat soil contained a moderate C-organic (16.31%), high nitrogen (1.09%) and moderate C/N ratio (15.01).…”
supporting
confidence: 88%
“…The absence of vegetation over soil surface caused low SOM, since it was continuously oxidized. Low SOM content (±28.05%) in the average was also reported in Mappy Regency, especially in Bangge River Watershed, Papua [12]. 5.…”
Section: Soil Physical Characteristicssupporting
confidence: 53%
“…Peat swamp forest is characterized by relatively dense canopy cover, wet soils, low light intensity, and rich leaf litter on the forest floor. Peat swamp is naturally often waterlogged and the water surface and peat surface are highly acidic (Page et al 1999;Tanjung et al 2020). The Pematang Gadung Village Forest area is a coastal peat dome located between the Pawan and Pesaguhan Rivers.…”
Section: Habitat Characteristics Of Nepenthesmentioning
confidence: 99%